1999
DOI: 10.1046/j.1442-200x.1999.4121036.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid and lipoprotein profile in children with iron deficiency anemia

Abstract: Patients with IDA are also deficient in macronutrients. The low atherogenic serum lipid profile of IDA is not a direct result of iron deficiency itself, but related to decreased energy and protein intakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
8
2
Order By: Relevance
“…A number of studies have suggested links between Fe deficiency anemia and altered lipid metabolism; however, these studies do not all find the same effects. For example, children with Fe deficiency anemia have either increased plasma cholesterol concentrations (44) or reduced plasma cholesterol concentrations (8). In animal studies, maternal dietary Fe restriction during gestation either increases plasma lipid concentrations in the offspring (40) or has no effect on plasma cholesterol concentrations in the adult offspring (29).…”
mentioning
confidence: 99%
“…A number of studies have suggested links between Fe deficiency anemia and altered lipid metabolism; however, these studies do not all find the same effects. For example, children with Fe deficiency anemia have either increased plasma cholesterol concentrations (44) or reduced plasma cholesterol concentrations (8). In animal studies, maternal dietary Fe restriction during gestation either increases plasma lipid concentrations in the offspring (40) or has no effect on plasma cholesterol concentrations in the adult offspring (29).…”
mentioning
confidence: 99%
“…However a study on ID Korean girls (14-19 years) found reduced levels of TG in severe IDA while another study 9 on Turkish children with IDA found no effect on either TG or VLDL levels.…”
mentioning
confidence: 89%
“…However, Ece et al 9 in a study on IDA children reported reduced LDL levels, which returned to control levels after the iron therapy. Serum TC did not show any significant alteration in the IDA group while previous studies have reported variable results in relation to TC, with some studies reporting it as normal, 10,20 while others reporting low levels.…”
mentioning
confidence: 91%
See 2 more Smart Citations